# How do you solve #10 + 2/3t=6#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 10 + (2/3)t = 6, you would first subtract 10 from both sides to isolate the term involving t. Then, you would multiply both sides by 3/2 to solve for t. The steps would be:

- Subtract 10 from both sides: 10 + (2/3)t - 10 = 6 - 10
- Simplify: (2/3)t = -4
- Multiply both sides by 3/2 to isolate t: (3/2)(2/3)t = -4(3/2)
- Simplify: t = -6

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7